A note on the Lie polynomial (x+y)^p-x^p-y^p - Jiao, Rongzheng (Tamkang Journal of Mathematics, 2006)
Using the techniques of group action on a set, we will give an elementary ane complete proof in this paper that the Lie polynomial (x+y)^p-x^p-y^p over prime field F_p is a sum of Lie brackets, with p a rational prime.